THE PROBLEMS FACED BY THE UNIVERSITY STUDENTS IN SPEAKING PERFORMANCE AT BINA SARANA INFORMATIKA UNIVERSITY - tarina dashela; Yeni Mustika (Faculty of Letters Universitas Balikpapan, 2024)
This research focused to analyze English speaking skill problems encountered by the students. The participants of this research was 30 students of second-semester at Bina Sarana Informatika University. The data of this research were conducted through speaking test and interview. The interview showed to see the students who got low score in speaking performance. The findings from the speaking test showed that the students faced the problems in four aspect of speaking skills such as grammar, pronunciation, vocabulary, and self-confidence. The students did not know how to express and pronounce the words because they did not have basic English skills. Moreover, they are afraid to make mistake in speaking English.